The Halal Industry as a Driver of Economic Growth: A Study of Indonesian Food and Beverage Products - Najmi Maulita Amaliya; Fathor Rahman; Dyan Irawati; Musleh, Musleh; Lailatul Maghfiroh (Al-Iffah: Journal of Islamic Sciences Research, 2025)
The halal industry in Indonesia plays a strategis role in supporting national economic growth, particulary in the food and beverage sector. Since the enactment of the Halal Product Assurance Law (UU JPH) in 2014, strengthening the halal system has been increasingly coordinated through the Halal Product Assurance Agency (BPJPH). The purpose of this study is to analyze the halal industry’s contribution to national economic growth and identify challenges and strategies for its development in Indonesia. This study uses a qualitative method based on a literature review to examine the role of the halal industry in the national economy. The results indicate that the value of national halal product consumption is projected to reach US$282 billion by 2025, a 53% increase compared to 2020. The halal food and beverage sector makes the largest contribution to GDP through increased production, investment, and exports. Halal certification increases consumer trust and product competitiveness, although challenges remain in the certification process, infrastructure, and halal literacy. Strengthening the halal ecosystem through certification digitalization, islamic financing, and cross-sector collaboration are key strategies to make Indonesia a global center of the halal economy.